Agro-climate tools for a new climate-smart agriculture - Hansen, James; Coffey, Kevin (2011)
The way we produce food must adapt to a variable and changing climate. And key to achieving this is to improve the link between climate information and agricultural practices, especially those of smallholder farmers in developing countries. ‘Agro-climate tools’ do just that and some are introduced here. This is also a call to government ministers and donors to consider investing in such tools as relatively low-cost means to rapidly and effectively improve food security in an increasingly uncertain world.